(untitled) (Northern University Journal of Law, 2015)
This paper is designed to throw an insight into the legal framework of corporate rescue procedure of the companies in the case of insolvency which are generally governed by insolvency laws. It analyzes the present status and application of insolvency law of our country in the context of companies, by comparing the same with the law of England & Wales. The paper contains major provisions of the present law relating to corporate rescue procedures in English jurisdiction including landmark judgments given in that context. By this comparison, the paper aims to provide the reader with the instigation of thought for making possible improvements in our present law by way of implementing rescue procedures for companies which are in financial difficulties. Northern University Journal of Law Vol.IV 2013; p.57-65